Assessing the prevalence of unethical behaviour in the South African police service - Maxwell Haurovi; Alouis Chilunjika (Insights into Regional Development)
States have always used their law enforcement and security organs to ensure that communities are peaceful, liveable and tranquil. These include the police services such as the South African Police Service (SAPS), which serves the same function in the local contexts. In pursuing its mandate, the SAPS uses preventative and curative strategies to establish community peace and calm. These are ensured through various policy and statutory prescriptions, including the Constitution and Code of Conduct. The study uses Adam Smith’s theory of Moral Sentiments to unpack and assess unethical conduct within the SAPS. Using the qualitative methodological approach, hinged on an interpretive research philosophy, the study gathered data from written documents. The collected data was analysed using content and thematic analysis techniques. The study established that upholding ethical and professional conduct by police officers within the crime prevention mandate of the SAPS remains problematic. SAPS encountered challenges like police corruption, bribery, illegal protection, and extortion. The study thus makes various recommendations, including a professionalised recruitment process for the SAPS.